AN ANALYSIS OF ENGLISH DEPARTMENT STUDENTS’ ACCURACY IN TRANSLATING NATURAL SCIENCE TEXT FROM ENGLISH INTO BAHASA INDONESIA - Yuri Azirovi; An Fauzia Rozani Syafe’i; Fitrawati Fitrawati (Journal of English Language Teaching, 2016)
This was a descriptive quantitative research which aimed to identify the English Department 2013 students’ accuracy in translating natural science text from English into bahasa Indonesia and to describe their accuracy problems in translation. From 94 students, 38 among them were chosen randomly as the sample by using quota random sampling. The data in this research were the students’ translations which would be assessed by three inter raters for each text. The researcher used accuracy rating instrument proposed by Nababan in order to analyze the accuracy of students’ translations. The findings showed that there were 30 students who had less accurate translation in translating biology text; 12 students who had less accurate translation in translating physics text; and 31 students who had less accurate translation in translating chemistry text. The rests of the students were categorized into inaccurate translation. Thus, there was no student who had an accurate translation. The findings also showed that the students faced accuracy problems including lexical meaning, grammatical meaning, contextual meaning, and textual meaning. It could be concluded that the students’ accuracy in translating natural science texts were mostly in less accurate category. As a result, the students needed to have more exercises in order to have an accurate translation.